ANALISIS PERAN KEMITRAAN STRATEGIS DALAM MENINGKATKAN PERTUMBUHAN UMKM MELALUI EDUKASI BISNIS DI KOTA MAKASSAR - Hendra Gunawan; Besse Qur’ani; Abdul Gafar Samalam; M. Fahrul Husni (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the role of strategic partnerships in enhancing SME growth through business education among food-sector SMEs in Makassar City. The research employs a quantitative approach using a survey method involving SME owners selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares with the SmartPLS software. The findings indicate that strategic partnerships have a positive and significant effect on business education and SME growth. Business education also has a positive effect on SME growth. Furthermore, business education acts as a mediating variable that strengthens the relationship between strategic partnerships and SME growth. These findings suggest that strategic partnerships integrated with business education initiatives can enhance entrepreneurial capabilities and support sustainable SME growth. This study contributes to the literature on entrepreneurship and strategic management and provides practical implications for strengthening the SME ecosystem through collaborative partnerships and more effective business education programs.